Experimental Investigation of Silica Nanoparticle Assisted Lignosulfonate Surfactant for Chemical Enhanced Oil Recovery (EOR) Flooding - Sarah Dampang; Muhammad Mufti Azis; Ahmad Tawfiequrrahman Yuliansyah; Suryo Purwono (ASEAN Journal of Chemical Engineering, 2024)
There has been significant interest in incorporating nanoparticles into surfactants to enhance the performance of chemical-enhanced oil recovery. This interest has arisen due to attempts to mitigate the decline in surfactant efficiency caused by various environmental factors within the reservoir. The primary objective of this study was to investigate how silica nanoparticles (SNP), combined with formulated sodium lignosulfonate (FSLS) surfactants, can improve oil recovery from reservoirs. In this paper, we conducted an experimental study to assess the impact of SNP when mixed with FSLS surfactants. The aim was to evaluate whether SNP alters the characteristics of FSLS surfactants and to determine SNP's potential to enhance oil recovery. We conducted experiments to measure compatibility, interfacial tension, and core flooding. We identified the optimal conditions for an FSLS 1% wt + SNP 0.1% wt solution for chemical flooding test based on the experimental results. The chemical flooding results showed a significantly higher recovery factor (RF) in the presence of SNP, with a recovery of 60% of the initial oil in place (IOIP), compared to only FSLS, which had an RF of 23.53% IOIP. The resulting interfacial tension (IFT) value was 10-4 - 10-3 mN/m. The solutions showed good stability in a single phase, did not precipitate, and appeared clear. Therefore, using SNP combined with FSLS surfactants demonstrates excellent potential for enhancing chemical-enhanced oil recovery methods.